Preventing Disruptive Behavior via Classroom Management: Validating the Color Wheel System in Kindergarten Classrooms. (July 2016) - Watson, Tiffany L.; Skinner, Christopher H.; Skinner, Amy L.; Cazzell, Samantha; Aspiranti, Kathleen B.; Moore, Tara; Coleman, MariBeth
Evidence suggests that installing a classroom management system known as the Color Wheel reduced inappropriate behaviors and increased on-task behavior in second- and fourth-grade classrooms; however, no systematic studies of the Color Wheel had been disseminated targeting pre-school or kindergarten participants. To enhance our understanding of the Color Wheel System (CWS) as a prevention system, a multiple-baseline design was used to evaluate the effects of the Color Wheel on inappropriate vocalizations (IVs) in three general education kindergarten classrooms. Partial-interval time-sampling was used to record classwide IVs, which were operationally defined as any comment or vocal noise that was not solicited by the teacher. Time series graphs and effect size calculations suggest that the CWS caused immediate, large, and sustained decreases in IVs across the three classrooms. Teacher acceptability and interview data also supported the CWS. Implications related to prevention are discussed and directions for future research are provided.